Nanoelectronics, Circuits and Communication Systems Proceeding of NCCS 2017 - Nath, Vijay; Mandal, Jyotsna Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book features selected papers presented at Third International Conference on Nanoelectronics, Circuits and Communication Systems (NCCS 2017). Covering topics such as MEMS and nanoelectronics, wireless communications, optical communication, instrumentation, signal processing, Internet of Things, image processing, bioengineering, green energy, hybrid vehicles, environmental science, weather forecasting, cloud computing, renewable energy, RFID, CMOS sensors, actuators, transducers, telemetry systems, embedded systems, and sensor network applications in mines, it is a valuable resource for young scholars, researchers, and academics.
Classification of Medical Dataset Along with Topic Modelling Using LDA -- Cloud based Intelligent System for Supply Chain Management: A Future Roadmap for SCM Technologies -- The Impact of Knowledge Management and Data Mining on CRM in the Service Industry -- An Underground Mine Safety of Personnel's Using IoT -- Design and Implementation of an Energy Efficient, Low-Cost Robotic Solar Tracker -- Fast Squaring Technique for Radix Vicinity Numbers for Radix 2n±m with Reduced Computational Complexity -- Usage of Deep Learning in Epileptic Seizure Detection through EEG Signal -- Chaos based Colour Image Encryption using Microcontroller ATMEGA 32 -- Hand Gesture Recognition: A Survey -- Robust Voiceprint based Audio Watermarking using Wavelet Transform -- Study and Design of Smart Embedded System for Aviation System: A review -- Denial of Service Attacks.
Keywords: Telecommunication; Electronics; Wireless communication systems; Mobile communication systems; Communications Engineering, Networks; Electronics and Microelectronics, Instrumentation; Wireless and Mobile Communication